Multiple Myeloma Complicated With Bronchiolitis Obliterans Syndrome After Allogeneic Haematopoietic Stem Cell Transplantation and Subsequently Underwent Lung Transplantation Successfully: A Case Report - Shih‐Wei Huang; Ko‐Wei Chang; Wei‐Hsun Chen; Pin‐Li Chou; Chien‐Hung Chiu; Yun‐Hen Liu; Chih‐Wei Wang; Hsiao‐Wen Kao; Tung‐Liang Lin; Shaw‐Woei Leu; Han‐Chung Hu; Kuo‐Chin Kao (Respirology Case Reports)
ABSTRACT Allogeneic haematopoietic stem cell transplantation (allo‐HSCT) is an effective treatment for multiple myeloma; however, the development of chronic graft‐versus‐host disease remains a significant challenge. Bronchiolitis obliterans syndrome (BOS) is one of the complications. Even with available medications for treatment, the prognosis of BOS remains poor. We present a 32‐year‐old female with multiple myeloma experienced BOS 6 months after allo‐HSCT. Even with medical treatment, her clinical condition and pulmonary function was deteriorating. Based on the indication of a BODE (Body‐mass index, Obstruction, Dyspnoea and Exercise) index of 7, she underwent bilateral lung transplantation 33 months after allo‐HSCT. Three months post‐operation, there was a significant improvement in pulmonary function. After approximately 5 years of follow‐up, her lung function remains stable, and she is able to work and live a normal life. Lung transplantation may be an effective therapeutic strategy for BOS developed after allo‐HSCT.